PENERAPAN ASAS OPORTUNITAS DALAM HUKUM PIDANA DI INDONESIA DITINJAU DARI HUKUM ISLAM - Salinah salinah (IAIN Langsa, 2017)
Law enforced one of them is to meet the sense of justice. Everyone is equal before the law. In the criminal procedure law we recognize several principles which one of them is the principle of opportunity. The principle of self-participation is not actually mentioned in the Criminal Procedure Code but is implied. Whereas if we look back at previous criminal cases, the principle of opportunism is real applied to some people who are considered influential in this country. Whereas whoever he is he does not have impunity, just like ordinary people. However, there are other considerations in enacting this principle. Which of these considerations is the Attorney-General's authority. Furthermore, if we look from the view of Islamic law, we clearly know that whoever it is, it is equal before God and His law.